1997
DOI: 10.1007/pl00012284
|View full text |Cite
|
Sign up to set email alerts
|

Selective Treatment of Differentiated Thyroid Carcinoma

Abstract: Over a period of 20 years 84 papillary and 82 follicular carcinomas operated on by one surgeon and examined by one pathologist were documented prospectively, treated selectively, and followed for 1 to 20 years (median 7 years). Tumors with a low risk of recurrence or incurable disease-i.e., papillary carcinoma pT1-3 N0 M0 (n = 56) and minimally invasive follicular carcinoma (n = 37)-were treated by a limited-radicality hemithyroidectomy or total thyroidectomy without radioiodine in 79 of the 93 cases (85%). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
2
10

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 20 publications
8
31
2
10
Order By: Relevance
“…In addition, our patients' characteristics are comparable to previous hospital or register based cohorts (7,14). Moreover, female-to-male ratio, percentage of follicular tumors or frequency of recurrences in our study group do not differ markedly from previous studies (7,15,16). The histology of the tumor is one of the major prognostic factors identified.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, our patients' characteristics are comparable to previous hospital or register based cohorts (7,14). Moreover, female-to-male ratio, percentage of follicular tumors or frequency of recurrences in our study group do not differ markedly from previous studies (7,15,16). The histology of the tumor is one of the major prognostic factors identified.…”
Section: Discussionsupporting
confidence: 79%
“…The mean age of our patients was closer to that of patients studied by Matsubayashi et al (19), but we could not show any significant difference between TILs and tumor recurrence. Several studies (14,15,21) have shown that an unfavorable outcome is associated with age. We found that age over 60 years was related to a higher risk of tumor recurrence and cause-specific mortality, confirming previous findings (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20,[24][25][26][27][28][29]31 Indeed, recommendations and consensus guidelines advocating total or near-total thyroidectomy in high-risk PTCs, but not necessarily in single, small, low-risk, intrathyroidal lesions, are not based on evidence demonstrating improved DSS, but rather on an understanding of the disease being multifocal with an increased risk of recurrence and the option to treat small residual thyroid cancer with RIA more effectively. 42,43 In addition, proponents of limited resection base their strategy on publications reporting increased postsurgical complications with more extensive resection.…”
Section: Extent Of Resectionmentioning
confidence: 99%
“…Indeed, many investigators found that more extensive resection of DTC with total or near-total thyroidectomy results in a lower incidence of local recurrences, although it does not influence DSS. [15][16][17][18][19][20][21] Recently, Bilimoira et al 22 showed a survival benefit after total thyroidectomy over lobectomy in PTC larger than 1 cm analyzing a cancer registry database. Proponents of limited resection base their strategy on publications reporting that postsurgical complications increased with more extensive resection.…”
mentioning
confidence: 99%
“…In our series, it is a good prognostic system, although it was outperformed by the EORTC system. Gemsenjäger et al (45), in a study on 84 papillary and 82 follicular carcinomas, also found it to be valuable as a prognostic system. Although it is not the most predictive system, it has the advantage of being internationally recognized making the comparison between series easier.…”
Section: Discussionmentioning
confidence: 96%